Electricity in hospitals: solutions based on economies of scale = Energía eléctrica en hospitales: soluciones basadas en economías de escala - Sánchez Barroso, Gonzalo; Gomez Chaparro, Miguel; Carretero Ayuso, Manuel J.; García Sanz Calcedo, Justo (Building & Management, 2019)
Due to the characteristics of the operation of a hospital, their demand for supplies and the need for uninterruptibility, hospital becomes an energy-intensive building. Currently, energy policies of building operation are based on strategies of energy saving and efficiency. In order to carry them out, it is necessary to get information about the consumption profile of the target building and make decisions based on it. The aim of this work is to analyse the different options for contracting an electricity supply for large consumers, such as hospitals, in an attempt to achieve the greatest savings in energy costs. The possibilities of managing the purchase of energy from these large consumers were discussed and analysed. It was concluded that there is a wide range of contracting possibilities beyond the traditional ones (fixed or indexed contract). It also highlighted the need for qualified personnel to assume the responsibility of studying the different modalities of purchase since it will provide an enormous benefit to hospital management.ResumenDebido a las características del funcionamiento de un hospital, su demanda de suministros y la necesidad de ininterrumpibilidad del mismo, el hospital se convierte en un edificio energéticamente intensivo. En la actualidad, las políticas energéticas de explotación de edificio se basan en estrategias de ahorro y eficiencia energética. Para poder llevarlas a cabo, es necesario disponer de la información acerca del perfil de consumo del edificio objetivo y tomar decisiones en base a ello. El objetivo de este trabajo es analizar las diferentes opciones de contratación del suministro eléctrico para grandes consumidores, como hospitales, presenten el mayor ahorro de costes energéticos. Se discutieron y analizaron las posibilidades de gestión de la compra de energía a estos grandes consumidores. Se destacó como principal conclusión el amplio abanico de posibilidades de contratación más allá de los tradicionales (contrato fijo o indexado). Asimismo, se destacó la necesidad de disponer de personal capacitado para asumir la responsabilidad de estudiar las diferentes modalidades de compra puesto que aportará un enorme beneficio a la gestión hospitalaria.